Neural network evaluation of model-based residuals in fault detection of time delay systems - Zítek, Pavel; Mánková, Renata; Hlava, Jaroslav (Zielona Góra: Uniwersytet Zielonogórski)
Model-based fault detection becomes rather questionable if a supervised plant belongs to the class of systems with distributed parameters and significant delays. Two methods of fault detection have been developed for this class of plants, namely a method of functional (anisochronic) state observer and a modified internal model control scheme adopted for that purpose.
Keywords: model-based fault detection; anisochronic model; state observer; internal model control; artificial neural networks